Two Africas? Why Africa's "growth miracle" has barely reduced poverty - Rumman Khan; Oliver Morrissey; Paul Mosley (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2019)
Growth improved substantially in most countries in sub-Saharan Africa (SSA) since 1990, but poverty in SSA as a whole has fallen by about a third, compared to by half or more in other developing regions. While some countries have had little or no success in reducing poverty, many have had significant achievements. The paper argues that inter-country differences, traceable to colonial experience, are crucial to understanding this varied SSA performance. This is based on a distinction between relatively labour-intensive smallholder' colonial economies and capital-intensive "extractive economies" exporting minerals and plantation crops. Because of the more equitable income distribution and African political inclusion generated in smallholder economies, at independence they were in a better position than extractive economies to translate growth into poverty reduction. Since the 1990s (when poverty data are available) the distinction in terms of poverty reduction can be observed. The empirical analysis estimates the growth elasticity of poverty using various specifications, some including inequality. There are two key robust findings: i) smallholder economies significantly outperform extractive economies in poverty reduction; and ii) growth rates do not differ on average between the two groups, but the growth elasticity of poverty is higher in smallholder economies.
Keywords: I32; N37; O10; O55; 330; Poverty; sub-Saharan Africa; colonial legacy; inclusive growth